Surface functionalized metal cluster and application thereof

By constructing a surface functionalized metal cluster layer on the surface of the lithium metal negative electrode of an all-solid lithium metal battery, the chemical properties of fluorine and iodine elements and the conductivity of the metal clusters are used to solve the problems of lithium dendrites growth, volume expansion and side reactions, and the cycle life and safety of the battery are significantly improved.

CN119852309AActive Publication Date: 2025-04-18SHANGHAI FIRM LITHIUM NEW ENERGY TECH CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510329752.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-04-18
Estimated Expiration
2045-03-20

AI Technical Summary

Technical Problem

The lithium metal negative electrode in all-solid lithium metal batteries faces problems such as lithium dendrites growth, volume expansion and side reactions, which affect the cycle life and safety of the battery.

Method used

Surface functionalized metal clusters (containing fluorine and iodine elements) are used to modify the surface of the lithium metal negative electrode, and LiF is generated by reacting fluorine elements with lithium to form a stable SEI film. The iodine elements slow down the migration speed of lithium ions, and the metal clusters improve the interface conductivity and promote the uniform transmission of lithium ions.

Benefits of technology

Effectively inhibit the growth of lithium dendrites, improve interface contact, improve the circulation performance and Coulomb efficiency of lithium metal negative electrodes, and significantly increase the cycle life and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852309A_ABST
    Figure CN119852309A_ABST
Patent Text Reader

Abstract

The invention discloses a surface functionalized metal cluster and application thereof, and relates to the field of battery materials. The metal cluster comprises a metal core and a surface functionalized layer, the metal core is selected from one or more of copper (Cu), silver (Ag) and gold (Au), and the surface functionalized layer comprises a fluorine element (F) and an iodine element (I). The metal cluster is applied to the surface of an all-solid-state lithium metal negative electrode and can effectively inhibit growth of lithium dendrites, relieve volume expansion and improve interface stability, so that the performance of an all-solid-state lithium metal battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery materials, and in particular to a surface functionalized metal cluster and its application in an all-solid-state lithium metal negative electrode, in particular to a metal cluster containing fluorine and iodine elements, for improving the performance of an all-solid-state lithium metal battery. Background Art

[0002] All-solid-state lithium metal batteries have attracted much attention due to their high energy density and safety. However, the lithium metal anode has problems such as lithium dendrite growth, volume expansion and side reactions with electrolytes during the charge and discharge process, which seriously affect the cycle life and safety of the battery. Therefore, how to inhibit lithium dendrite growth, alleviate volume expansion and reduce side reactions is the key to the research of all-solid-state lithium metal batteries.

[0003] In response to the above problems, researchers have proposed a variety of solutions, mainly including: Electrode structure design: By designing a three-dimensional porous structure or introducing other conductive skeleton materials, the uniform deposition of lithium ions can be guided and volume expansion can be alleviated.

[0004] Interface modification: By constructing an artificial protective layer on the surface of the lithium metal negative electrode, side reactions can be inhibited and interface stability can be improved.

[0005] Special challenges of all-solid-state lithium metal batteries: Compared with traditional liquid lithium-ion batteries, all-solid-state lithium metal batteries use solid electrolytes instead of traditional liquid electrolytes, which have higher safety and energy density potential. However, all-solid-state lithium metal batteries also face some unique challenges: Poor interface contact: The interface contact between the solid electrolyte and the lithium metal anode is poor, resulting in excessively high interface impedance, which affects the performance of the battery.

[0006] Poor interfacial chemical stability: Some solid electrolytes have poor chemical stability with lithium metal and are prone to side reactions, leading to deterioration of interfacial performance.

[0007] The transport rate of lithium ions in solid electrolytes is low: Compared with liquid electrolytes, the transport rate of lithium ions in solid electrolytes is low, which limits the rate performance of the battery.

[0008] Therefore, for all-solid-state lithium metal batteries, it is particularly necessary to develop effective interface modification strategies to improve the interfacial contact and chemical stability between the solid electrolyte and the lithium metal anode and to enhance the lithium ion transport efficiency.

[0009] The present invention is aimed at the problems existing in the above background technology and proposes a new interface modification strategy, that is, using surface functionalized metal clusters (containing fluorine and iodine elements) to modify the surface of lithium metal negative electrode. This strategy aims to combine the advantages of fluorine and iodine elements, as well as the good conductivity of metal clusters, to achieve the following purposes: Fluorine is used to react with lithium to generate LiF, forming a stable SEI film, improving interface stability and reducing side reactions.

[0010] The larger ionic radius of iodine plays a steric role in the lithium deposition process, slowing down the migration speed of lithium ions and thus inhibiting the rapid growth of dendrites.

[0011] The good conductivity of metal clusters is utilized to improve the interfacial conductivity and promote the transport of lithium ions.

[0012] Through the above strategies, the present invention aims to solve the interface problems faced by the lithium metal negative electrode in the all-solid-state lithium metal battery and improve the cycle life, rate performance and safety of the battery. Summary of the invention

[0013] In view of this, the purpose of the present invention is to provide a surface functionalized metal cluster and its application, the functionalized layer can effectively inhibit the growth of lithium dendrites, improve the interface contact, and improve the cycle performance and coulomb efficiency of the lithium metal negative electrode, and is particularly suitable for all-solid-state lithium metal battery systems. The present invention effectively improves the interface contact between lithium metal and solid electrolyte by constructing a surface functionalized metal cluster layer containing fluorine and iodine elements on the surface of lithium foil, and has potential advantages in large-scale production.

[0014] The surface functionalized metal clusters are deposited on lithium metal, on the one hand, by guiding the uniform deposition of lithium ions. On the other hand, by providing a buffer space or enhancing the mechanical strength of the electrode. On the other hand, by forming a stable interface protection layer. This method provides an effective solution to the key problems in the development of all-solid-state batteries. The surface functionalized metal clusters of the present invention are applied to all-solid-state lithium metal batteries and can still maintain more than 90% of the capacity after 500 cycles, and the cycle life is increased by about 800%.

[0015] To achieve the above purpose, the technical solution adopted by the present invention is as follows: <First aspect> A surface functionalized metal cluster for a lithium metal negative electrode, wherein the surface functionalized metal cluster is coated or deposited on the surface of the lithium metal negative electrode and is prepared by a method comprising the following steps: The surface of the metal core is treated to form a surface functionalized layer, thereby obtaining a surface functionalized metal cluster; The surface treatment is fluorination and / or iodination treatment, and the surface functionalization layer is composed of corresponding metal fluorides and / or metal iodides.

[0016] Preferably, the metal core is a metal nanocluster with a cubane structure, and the average particle size is 1-100 nm. The metal of the metal core includes one or more of Cu, Ag, and Au, preferably Cu and / or Ag.

[0017] Preferably, the metal fluoride and / or metal iodide in the surface functionalization layer is a cubane-type structure. The cubane-type structure is represented by M4X4 ( Figure 4 ), M is one of Cu, Ag, Au, X is one of F, I; preferably Cu4F4, Ag4I4, Cu4I4 and Ag4F4. The metal nanocluster is [Cu4F4] n or [Ag4I4] n , the cubane-type structure forms metal nanoclusters.

[0018] Preferably, the preparation method of the metal core comprises one of chemical reduction, solvothermal, microemulsion and vapor deposition. The preparation step of the metal core is: in an inert gas protection environment, the metal nanoclusters are prepared by chemical reduction, solvothermal, microemulsion or vapor deposition.

[0019] Preferably, the preparation method of copper nanoclusters is as follows: slowly drop NaBH4 solution into CuCl2 solution, and the copper nanoclusters are obtained after stirring and reacting. The molar ratio of NaBH4 to CuCl2 is 1.2-1.8:3. The stirring reaction time is 30-40 min. The content of NaBH4 solution is 0.01-0.025 mol / 50 ml; the content of CuCl2 solution is 0.02-0.04 mol / 20 ml.

[0020] Preferably, the preparation method of silver nanoclusters is as follows: AgNO3 solution and PVP solution are mixed to obtain a mixed solution; then KI solution is added to the mixed solution, and the silver nanoclusters are obtained by stirring the mixture. The mass ratio of KI, AgNO3 and PVP is 0.15-0.2:0.15-0.2:0.1. The stirring reaction time is 30-40 min. The content of KI solution is 0.15-0.2g:50ml; the content of AgNO3 solution is 0.15-0.2g:50ml; the content of PVP solution is 0.4-0.6 wt%.

[0021] Preferably, the microemulsion method comprises: (1) preparing aqueous solutions of metal salt and halide salt respectively; (2) dissolving the surfactant in the oil phase solvent, and adding metal salt and halide salt aqueous solutions respectively to form a reverse microemulsion; (3) mixing two reverse microemulsions and reacting them under stirring; (4) Washing and drying the product.

[0022] Preferably, the average particle size is 1-10 nm.

[0023] Preferably, the step of surface treatment is: preparing a fluoride salt and / or an iodide salt into a salt solution, dropping the solution into the metal core dispersion, and stirring the solution to react, thereby obtaining a surface functionalized metal cluster.

[0024] The mass ratio of the metal core to the fluoride salt and / or the iodide salt is 1:1-3.

[0025] Fluoride salts include one or more of LiF, NaF, and AgF; iodide salts include one or more of LiI, NaI, and KI. Other halides, such as metal chlorides, are not as good as metal fluorides and iodides in terms of stability, corrosion resistance, surface energy, and specific electronic properties of the functional layer, and cannot meet application requirements. In addition, the chlorination reaction is more difficult to control accurately, and it is easy to over-react or produce by-products, which affects the quality and performance of the surface functional layer.

[0026] The solubility of the salt solution is 0.01-0.1 g / ml, the content of the metal core in the metal core dispersion is 0.01-0.05 g / ml, and the stirring reaction time is 20-30 hours.

[0027] The surface of the obtained surface functionalized metal cluster is fluorine and / or iodide with a cubane-type structure, and the interior is a metal cluster. The surface treatment reaction tends to occur on the surface of the metal core, forming a metal-halogen (such as Cu-F, Ag-I) surface functionalization layer, while the interior remains in a metallic state. This is because: the halogen ion (F - or I - The oxidation reaction of fluorine and metal (such as Cu, Ag) occurs preferentially on the surface of the metal core with high surface energy, forming a stable halide passivation layer to prevent further reactions inside. Fluorine and / or iodine are located on the surface of the metal cluster. When a small amount of fluorine and iodine is added, fluorine reacts with lithium to form a stable SEI film, and iodine slows down the migration of lithium ions.

[0028] The reaction of surface functionalization of Cu and Ag metal clusters is as follows: Oxidation-reduction reaction (metal core is reduced): Cu 0 (Surface) +2F - →CuF2 (surface); Coordination-driven surface reconstruction: Ag 0 (Surface)+I - →AgI (surface).

[0029] The surface functionalized metal core of the present invention comprises a metal core and a surface functionalized layer, wherein the metal core is selected from one or more of copper (Cu), silver (Ag), and gold (Au), and the surface functionalized layer comprises fluorine (F) and iodine (I).

[0030] <Second Aspect> A lithium metal anode containing surface functionalized metal clusters is prepared by a method comprising the following steps: S1, performing surface treatment on the surface of the metal core to form a surface functionalized layer to obtain a surface functionalized metal cluster; S2. Modifying the surface functionalized metal clusters on the surface of the lithium negative electrode to obtain a lithium metal negative electrode containing the surface functionalized metal clusters.

[0031] Preferably, step S2 is performed under an inert gas protection environment.

[0032] Preferably, in step S2, the lithium negative electrode is pretreated: in an inert gas protection environment, the surface of the lithium foil is mechanically scraped to remove the oxide layer and impurities on the surface.

[0033] Preferably, in step S2, the modification method includes one of coating, deposition, and in-situ growth.

[0034] Preferably, in step S2, the coating method includes one of spin coating, dip coating, spray coating or scraper coating. The coating method is preferably spin coating.

[0035] Preferably, in step S2, the coating is to disperse the surface functionalized metal clusters in a non-protonic polar solvent, and then coat the resulting dispersion on the surface of the lithium negative electrode. The non-protonic polar solvent is selected from N-methylpyrrolidone (NMP), acetonitrile (ACN), dimethylformamide (DMF) or anhydrous ether. The content of the surface functionalized metal clusters in the dispersion is 0.1-0.2g / 10ml.

[0036] Preferably, in step S2, the lithium negative electrode is a lithium metal negative electrode or a lithium alloy negative electrode and an intercalation negative electrode material thereof, preferably lithium foil.

[0037] Preferably, in step S2, the obtained lithium metal negative electrode comprises a base lithium metal negative electrode and a modified layer, and the modified layer comprises surface functionalized metal clusters.

[0038] <Third Aspect> Application of a lithium metal negative electrode containing a surface functionalized metal cluster in an all-solid lithium alloy secondary battery. Application of a surface functionalized metal cluster for a lithium metal negative electrode in an all-solid lithium alloy secondary battery with a lithium alloy as a negative electrode also falls within the scope of protection of the present invention.

[0039] An all-solid-state lithium metal secondary battery comprises a solid electrolyte, a positive electrode and the above-mentioned lithium metal negative electrode containing surface functionalized metal clusters.

[0040] Preferably, the solid electrolyte includes a polymer electrolyte, an oxide electrolyte and a sulfide electrolyte.

[0041] Preferably, the positive electrode active material of the lithium metal battery is one of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium manganese phosphate, lithium titanate, lithium nickel oxide, and lithium manganese oxide.

[0042] Compared with the all-solid-state lithium metal battery in the prior art, the beneficial effects of the present invention are: (1) Improved interface contact: In traditional all-solid-state lithium metal batteries, poor interface contact between the lithium metal negative electrode and the solid electrolyte is a long-standing bottleneck problem. The present invention effectively improves the interface contact between lithium metal and the solid electrolyte by constructing a surface functionalized metal cluster layer containing fluorine and iodine elements on the surface of lithium foil. The metal cluster can increase the actual contact area and reduce the interface resistance.

[0043] (2) Inhibition of side reactions: Lithium metal has extremely high chemical activity and is prone to side reactions with solid electrolytes. The surface functionalized metal cluster layer in the present invention can serve as a "buffer layer" to effectively isolate lithium metal from the solid electrolyte, reduce or even inhibit direct contact between the two, and thus reduce the occurrence of side reactions. For example, LiF generated by the reaction of fluorine and lithium helps to form a stable SEI film.

[0044] (3) Regulating ion transport and inhibiting lithium dendrite growth: The ionic conductivity of solid electrolytes is usually lower than that of liquid electrolytes, and the ion transport behavior at the interface is crucial to the performance of the lithium metal negative electrode. In the present invention, the larger ionic radius of the iodine element can play a steric hindrance role in the lithium deposition process, slowing down the migration speed of lithium ions, thereby inhibiting the rapid growth of lithium dendrites. The metal clusters themselves provide good electronic conductivity and promote uniform ion transport at the interface.

[0045] (4) The preparation method has certain universality and potential advantages in large-scale production: The present invention adopts a variety of mature preparation technologies (such as chemical reduction method, solvothermal method, microemulsion method and vapor deposition method), has certain universality, and can achieve large-scale production by optimizing process parameters.

[0046] (5) Compatible with a variety of solid electrolytes: The metal clusters and functionalized layer materials used in the present invention generally have high chemical stability and electrochemical stability, and have good compatibility with various solid electrolytes (including polymers, oxides, sulfides, etc.), and can be widely used in various all-solid-state lithium metal battery systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings: Figure 1 This is a graph showing the cycling performance of surface functionalized metal clusters applied to all-solid-state lithium metal in Example 1; Figure 2 This is a diagram of the coulombic efficiency of the surface functionalized metal clusters applied to all-solid-state lithium metal batteries in Example 1; Figure 3 This is a comparison chart of the cycle performance of the all-solid-state lithium metal battery of Example 1 of the present invention and Comparative Example 1; Figure 4 This is a schematic diagram of the structure of the metal clusters of the surface functionalized layer of the present invention; Figure 5 The XRD diffraction patterns of the copper nanoclusters and copper fluoride clusters in Example 1. DETAILED DESCRIPTION

[0048] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0049] Example 1 This embodiment provides a lithium metal negative electrode having a copper fluoride cluster layer, and this embodiment includes the following steps: S1. Preparation of copper nanoclusters: Add 50 mL of deionized water to a three-necked flask, heat to 60°C, and stir magnetically. Weigh 2.68 g of CuCl2·2H2O (0.015 mol), slowly add it to the hot water, and stir until completely dissolved to obtain a CuCl2 solution. Weigh 1.14 g of NaBH4 (0.03 mol), dissolve it in 20 mL of deionized water to prepare a NaBH4 solution.

[0050] Under vigorous stirring, slowly add NaBH4 solution to the CuCl2 solution. The color of the solution will quickly change from blue to brown-black, indicating that copper nanoclusters are generated. Continue stirring for 30 minutes to allow the reaction to proceed fully.

[0051] Reaction equation (simplified): CuCl2 + NaBH4 → Cu + H2 + NaCl + B(OH)3 After standing for a period of time, the product was separated by centrifugation and washed three times with deionized water and anhydrous ethanol to remove residual ions and byproducts. The washed product was dried in a vacuum drying oven at 60°C for 12 hours to obtain copper nanoclusters (particle size of about 2 nm).

[0052] S2. Surface fluorination treatment: In a glove box, 0.5 g of the dried copper nanoclusters were dispersed in 50 mL of anhydrous ethanol and ultrasonicated for 30 min to make them uniformly dispersed.

[0053] Weigh 0.84 g NaF (0.02 mol) and dissolve it in 20 mL deionized water to prepare a NaF solution.

[0054] Under stirring, the NaF solution was slowly added dropwise to the copper nanocluster dispersion.

[0055] The mixture was stirred in the glove box for 24 hours to allow the fluorination reaction to proceed fully.

[0056] S3. Post-processing: The reaction mixture was taken out from the glove box and the product was separated by centrifugation.

[0057] The samples were washed alternately with anhydrous ethanol and deionized water three times to remove residual NaF and by-products.

[0058] The washed product was dried in a vacuum oven at 60° C. for 12 hours to obtain copper fluoride clusters.

[0059] S4. Preparation of cluster dispersion: 0.1 g of dried copper fluoride clusters was dispersed in 10 ml of anhydrous ethanol and sonicated to obtain a uniform dispersion.

[0060] S5. Lithium sheet pretreatment: In a glove box, use a scraper to scrape off the oxide layer on the surface of the lithium sheet.

[0061] S6. Spin coating: The copper fluoride cluster dispersion was dropped onto the surface of the lithium sheet and spin-coated at 1000 rpm for 30 seconds to evenly coat the dispersion on the surface of the lithium sheet.

[0062] S7. Drying: The coated lithium sheet was dried in a vacuum drying oven in a glove box at 60° C. for 2 hours.

[0063] Figure 5 : The XRD diffraction patterns of the copper nanoclusters and copper fluoride clusters in Example 1. The characteristic peaks of the XRD diffraction pattern of the copper fluoride clusters are consistent with those of the nano-copper clusters, slightly shifted to the right, indicating that fluorine has entered the copper lattice, causing the lattice to shrink, but both are cubane-type structures.

[0064] Example 2 This embodiment provides a lithium metal negative electrode having a silver fluoride cluster layer, and this embodiment includes the following steps: S1. Preparation of silver nanoclusters Add 50 mL of deionized water to a three-necked flask, heat to 60°C, and stir magnetically. Weigh 0.17 g of AgNO3 (0.001 mol), slowly add it to hot water, and stir until completely dissolved to obtain an AgNO3 solution. Weigh 0.17 g of KI (0.001 mol), dissolve it in 50 mL of deionized water to prepare a KI solution. Weigh 0.1 g of PVP (as a stabilizer), dissolve it in 20 mL of deionized water to prepare a 0.5 wt% PVP solution.

[0065] Under vigorous stirring, slowly add KI solution to the AgNO3 / PVP mixed solution. The color of the solution will quickly change from colorless to turbid yellow, indicating that AgI nanoclusters are generated. Continue stirring for 30 minutes to allow the reaction to proceed fully.

[0066] After standing for a period of time, the product was separated by centrifugation, and the precipitate was washed three times with deionized water to remove residual KNO3 and PVP. The washed product was dried in a vacuum drying oven at 60°C for 12 hours to obtain silver nanoclusters (particle size of about 2 nm).

[0067] S2. Surface fluorination treatment In a glove box, 0.5 g of dried silver nanoclusters were dispersed in 50 mL of anhydrous ethanol and ultrasonicated for 30 minutes to make them uniformly dispersed. 0.84 g of NaF (0.02 mol) was weighed and dissolved in 20 mL of deionized water to prepare a NaF solution.

[0068] Under stirring, the NaF solution was slowly added dropwise to the silver nanocluster dispersion and the mixture was stirred in the glove box for 24 hours to allow the fluorination reaction to proceed fully.

[0069] S3. Post-processing The reaction mixture was taken out of the glove box and the product was separated by centrifugation. The product was washed alternately with anhydrous ethanol and deionized water three times to remove residual NaF and by-products. The washed product was dried in a vacuum drying oven at 60°C for 12 hours to obtain silver fluoride clusters.

[0070] S4. Preparation of cluster dispersion 0.1 g of dried silver fluoride clusters were dispersed in 10 mL of anhydrous ethanol and sonicated for 30 min to obtain a uniform dispersion.

[0071] S5. Lithium sheet pretreatment In a glove box, use a scraper to scrape off the oxide layer on the surface of the lithium sheet.

[0072] S6. Spin coating The silver fluoride cluster dispersion was dropped onto the surface of the lithium sheet and spin-coated at a speed of 1000 rpm for 30 seconds to evenly coat the dispersion on the surface of the lithium sheet.

[0073] S7. Drying The coated lithium sheet was dried in a vacuum drying oven in a glove box at 60° C. for 2 hours.

[0074] Example 3 This embodiment provides a lithium metal negative electrode having a copper iodide cluster layer, and this embodiment comprises the following steps: S1. Same as Example 1. S2. Surface iodination treatment In a glove box, 0.5 g of dried copper nanoclusters were dispersed in 50 mL of anhydrous ethanol and ultrasonicated for 30 min to make them uniformly dispersed. 0.83 g of KI (0.005 mol) was weighed and dissolved in 20 mL of deionized water to prepare a KI solution.

[0075] Under stirring, the KI solution was slowly added dropwise to the copper nanocluster dispersion and the mixture was stirred in the glove box for 24 hours to allow the iodination reaction to proceed fully.

[0076] S3. Post-processing The reaction mixture was taken out of the glove box and the product was separated by centrifugation. The product was washed alternately with anhydrous ethanol and deionized water three times to remove residual KI and by-products. The washed product was dried in a vacuum drying oven at 60°C for 12 hours to obtain copper iodide clusters.

[0077] S4. Preparation of cluster dispersion 0.1 g of dried copper iodide clusters was dispersed in 10 mL of anhydrous ethanol and sonicated for 30 min to obtain a uniform dispersion.

[0078] S5. Lithium sheet pretreatment In a glove box, use a scraper to scrape off the oxide layer on the surface of the lithium sheet.

[0079] S6. Spin coating The copper iodide cluster dispersion was dropped onto the surface of the lithium sheet and spin-coated at 1000 rpm for 30 seconds to evenly coat the dispersion on the surface of the lithium sheet.

[0080] S7. Drying The coated lithium sheet was dried in a vacuum drying oven in a glove box at 60° C. for 2 hours.

[0081] Comparative Example 1 This comparative example provides a lithium metal without a metal cluster layer; the steps are as follows Preparation of lithium metal anode: Commercial lithium copper composite tape (Tianjin Zhongneng Lithium Industry Co., Ltd.).

[0082] Comparative Example 2 (Copper Cluster Layer) This embodiment provides a lithium metal negative electrode having a copper cluster layer, and the steps are basically the same as those in Embodiment 1, except that the prepared copper nanoclusters are not subjected to fluorination treatment but directly coated.

[0083] Comparative Example 3 (Copper Fluoride Layer) This embodiment provides a lithium metal negative electrode having a copper fluoride layer, and the steps are basically the same as those in Embodiment 1, except that an equal amount of copper fluoride is directly taken for dispersion and coating.

[0084] Performance test case The products prepared in the above examples and comparative examples were assembled: in an inert gas glove box with a water and oxygen content of ≤0.01 ppm, Li6PS5Cl was used as the electrolyte layer, and the positive electrode was a NCM811 loading of 10 mg cm per unit area. -2 The electrode piece, the surface functionalized metal cluster lithium metal as the negative electrode layer, was assembled into an all-solid-state lithium metal battery. Finally, the external pressure-free cyclic discharge was carried out for two cycles of 0.1C charge and discharge, and then a long cycle test was carried out at 0.5C. The first efficiency was tested, and the capacity retention rate was tested after 500 cycles. The results are shown in Table 1: It can be seen from Table 1 that when using surface functionalized metal cluster lithium metal, it can exert higher first efficiency, capacity retention, and improve the performance of all-solid-state lithium metal life. Figure 1 It can be seen that Example 1 has excellent cycle ability and capacity retention; Figure 2 It can be seen that its excellent Coulomb efficiency. Figure 3 It can be seen that the cycle capacity of using surface functionalized metal cluster lithium metal is significantly better than that of comparative example 1.

[0085] Table 1

[0086] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A surface functionalized metal cluster, characterized in that: The surface functionalized metal cluster is coated or deposited on the surface of the lithium metal negative electrode and is prepared by a method comprising the following steps: The surface of the metal core is treated to form a surface functionalized layer, thereby obtaining a surface functionalized metal cluster; The surface treatment is fluorination and / or iodination treatment, and the surface functionalization layer is composed of corresponding metal fluorides and / or metal iodides; The metal core is a metal nanocluster having a cubane-type structure; The metal fluoride and / or metal iodide in the surface functionalization layer has a cubane-type structure.

2. The surface functionalized metal cluster according to claim 1, characterized in that: The metal of the metal core includes one or more of Cu, Ag, and Au.

3. The surface functionalized metal cluster according to claim 1, characterized in that: The surface treatment step is: preparing a fluoride salt and / or an iodide salt into a salt solution, dropping it into the metal core dispersion, stirring and reacting, and obtaining a surface functionalized metal cluster.

4. The surface functionalized metal cluster according to claim 3, characterized in that: The mass ratio of the metal core to the fluoride salt and / or the iodide salt is 1:1-3; and / or, the fluoride salt comprises one or more of LiF, NaF, and AgF; and / or, the iodide salt comprises one or more of LiI, NaI, KI; and / or, the saline solution has a solubility of 0.01-0.1 g / ml; And / or, the content of the metal core in the metal core dispersion is 0.01-0.05 g / ml.

5. A lithium metal negative electrode comprising the surface functionalized metal cluster as claimed in claim 1, characterized in that: Prepared by a method comprising the following steps: S1, performing surface treatment on the surface of the metal core to form a surface functionalized layer to obtain a surface functionalized metal cluster; S2, modifying the surface functionalized metal clusters on the surface of the lithium negative electrode, that is, obtaining a lithium metal negative electrode containing the surface functionalized metal clusters; The modification method includes coating and deposition.

6. The lithium metal negative electrode according to claim 5, characterized in that In step S2, the coating method includes one of spin coating, dip coating, spray coating, and scraper coating.

7. The lithium metal negative electrode according to claim 5, characterized in that In step S2, the coating is to disperse the surface functionalized metal clusters in a non-protonic polar solvent, and then coat the obtained dispersion on the surface of the lithium negative electrode; The aprotic polar solvent includes one or more of N-methylpyrrolidone, acetonitrile, dimethylformamide, and anhydrous ether.

8. Use of the lithium metal negative electrode as claimed in claim 5 in an all-solid-state lithium alloy secondary battery.

9. An all-solid-state lithium metal secondary battery, characterized in that: It comprises a solid electrolyte, a positive electrode and the lithium metal negative electrode as claimed in claim 5.

10. The all-solid-state lithium metal secondary battery according to claim 9, characterized in that: The solid electrolyte includes one of a polymer electrolyte, an oxide electrolyte, and a sulfide electrolyte; And / or, the active material of the positive electrode includes one of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium manganese phosphate, lithium titanate, lithium nickel oxide, and lithium manganese oxide.

Citation Information

Patent Citations

  • Lithium anode surface treatment method of lithium metal battery

    CN107093705A

  • Negative electrode for lithium metal battery and lithium metal battery comprising the same

    CN107394115A

  • Lithium iodide protective layer of lithium metal negative electrode as well as preparation process and application of lithium iodide protective layer

    CN114005959A

  • Preparation method and application of metal lithium foil with lithium metal modification layer

    CN117476879A

  • Method for producing isomorphous heterocaryosis cubic alkane type metal cluster compound molecular functional materials

    CN1888969A